Exploring prevention and control mechanisms of youth substance use: a case of North Wollo and Waghimra, Northeast Ethiopia - Asmare Wedi, Sindew; Abate, Biruk Beletew; Anmut Asres, Tesfa; Abera, Mohammed Aragaw; Bekele, Sentayehu Oljira; Sendekie, Ashenafi Kibret (Frontiers in Public Health, 2024)
BackgroundSubstance use among youths is a significant global and local issue. Youth who engage in substance use often experience various psychosocial, health, economic, and other problems. While governmental and non-governmental organizations in North Wollo and Waghimra Zones offer social services, their effectiveness in preventing and controlling substance use remains largely unstudied. This research aims to explore youth substance use prevention techniques and control mechanisms, youth participation, and potential challenges encountered by social service organizations.MethodsA qualitative case study design was employed in North Wollo and Waghimra Zones, Northeast Ethiopia. Purposive sampling was used to recruit participants. A total of 40 participants were involved, including 10 key informant interviews and 5 focus group discussions (FGDs) of youths (6 participants per group). The data collection instrument included a pre-tested semi-structured in-depth interview, an FGD guide, and an observation checklist. The collected data were analyzed thematically.FindingsPrevention efforts primarily focused on awareness-raising campaigns and advocacy programs. Control mechanisms were predominantly reactive, including measures such as regulating the substance trade, punishing drug dealers, destroying and burning drug paraphernalia, and closing substance trade centers. The study found limited youth involvement in substance use prevention and control initiatives. Several key challenges were identified in the prevention and control of youth substance use: limited government involvement, reliance only on reactive measures, low youth engagement, insufficient intersectoral collaboration, lack of community commitment, gaps in social institutions, absence of planned interventions, the economic role of substances, government ignorance, and the absence of comprehensive legal frameworks for prevention and control.Conclusion and recommendationThis study highlights a gap in prevention and control mechanisms, and engagement of youths, non-governmental as well as governmental bodies. This study recommends making evidence-based interventions and installing functional networks among sectors to deal with common issues. This issue also should not be left to a single organization and government agencies, families, religious, and educational institutions should play a leading role in tackling substance use burdens at the grassroots level.